The motivation of European Union mediation in civil conflicts. Issue 4 (2nd October 2018) - Scalera, Jamie E.; Wiegand, Krista E.
ABSTRACT: Since the EU has expanded its common security focus in the 1990s, this important regional organisation has become the most frequent mediator in low-level civil conflicts worldwide. Under what conditions is the European Union (EU) likely to become involved in mediation in civil conflicts? Is the participation in mediation only explained by the EU's bias toward its near abroad, or is the EU more strategic? Some scholars have suggested that the EU's regional bias for its near abroad is the key explanation for the onset of EU mediation, but we propose that the reality of EU mediation presents a more nuanced story. We posit three explanations based on mediator bias: regional bias, economic bias, and normative bias. Overall, we argue that the EU will mediate in civil conflicts that are in its near abroad, but also where the EU has economic bias and where the EU can exercise its normative power in highly intractable conflicts. We test our hypotheses using statistical analysis of the UCDP low-level civil conflicts data from 1993 to 2004 and Civil War Mediation data from 1974 to 2005. We find strong support for our hypotheses, determining key factors that reveal the EU's strategic onset of mediation.